Fatal subarachnoid hemorrhage following ischemia in vertebrobasilar dolichoectasia. Issue 27 (July 2016) - Sokolov, Arseny A.; Husain, Shakir; Sztajzel, Roman; Croquelois, Alexandre; Lobrinus, Johannes A.; Thaler, David; Städler, Claudio; Hungerbühler, Hansjörg; Caso, Valeria; Rinkel, Gabriel J.; Michel, Patrik
Abstract : Abstract: Vertebrobasilar dolichoectasia (VBD) is a chronic disorder with various cerebrovascular and compressive manifestations, involving subarachnoid hemorrhage (SAH). Occurrence of SAH shortly after worsening of clinical VBD symptoms has occasionally been reported. The goal of the study was to examine this association, in particular its pathophysiology, clinical precursor signs, time course, and outcome. To this end, in a retrospective multicenter study, we analyzed 20 patients with VBD and SAH in regard to preceding clinical symptoms, presence of vertebrobasilar thrombosis and ischemia, outcome and neuropathological correlates. Median age of the 7 female and 13 male patients was 70 years (interquartile range [IQR] 18.3 years). Fourteen patients (70%) presented with new or acutely worsening posterior fossa signs at a median of 3 days prior to SAH (IQR 2, range 0.5–14). A thrombus within the VBD was detected in 12 patients (60%). Thrombus formation was associated with clinical deterioration (χ 2 = 4.38, P = 0.04) and ponto-cerebellar ischemia (χ 2 = 8.09, P = 0.005). During follow-up after SAH, 13 patients (65%) died, after a median survival time of 24 hours (IQR 66.2, range 2–264 hours), with a significant association between proven ponto-cerebellar ischemia and case fatality (χ 2 = 6.24, P = 0.01). The data establish an association between clinical deterioration in patients with VBD, vertebrobasilar ischemia, and subsequent SAH. Antithrombotic treatment after deterioration appears controversial and SAH outcome is frequently fatal. Our data also indicate a short window of 3 days that may allow for evaluating interventional treatment, preferably within randomized trials.